Au-delà d’un manteau partagé: La poétique du vêtement dans la Vita Martini de Venance Fortunat - Pataki, Elvira (Verbum – Analecta Neolatina, 2017)
The present paper aims at examining the motif of textiles and dressing in the Latin hagiographic epos of Venantius Fortunatus. Key elements of the biographical tradition about Saint Martin of Tours, the images of cloths and the scenes of dress sharing seem to have special narrative and aesthetic functions in the poem while keeping their essential ascetic, thaumatourgic and anthropological importance. Being dressed appears as a symbol of being saved and protected, while a naked body can signify human vulnerability, temptation and sin at the same time. The stories woven into the poetic text about the different textiles of human or heavenly origin that are worn or shared by Saint Martin are used to illustrate the spiritual progress of the hero. Nevertheless, these episodes provide the unity of the narrative and renew some generic topos and skills of classical epic poetry (see the case of ecphrasis or enargeia) as well as formulate highly self-reflective metapoetic statements about creating a discourse. Finally, they raise questions about the hierarchy between visual arts (weaving, jewellery) and verbality, and reflect on the limits of human ways of expression in the representation of immaterial divine beauty.